Use of yoga in treatment and screening of eating disorders - Golebiowska, Maria; Golebiowska, Beata; Jasiński, Mirosław; Zienkiewicz, Ewa; Dubelt, Joanna (Journal of Education, Health and Sport, 2018)
Mental disorders are a common cause of human disability and early morbidity. Eating disorders, affecting greatly both mental and physical abilities of the patients, are a frequent diagnosis in modern societies (1-5% in women population) with low rate of full recovery (50%) and high morbidity (10-20%). The difficulties in compliance as well as importance of holistic approach, including restoring mind-body balance, improving body image disturbances and additional psychiatric symptoms, urge medicine to find complementary and alternative solutions for existing therapeutic options. Among those yoga, which involves meditation, body awareness, breathing techniques, light physical activity without significant BMI changes, seems to become a more and more popular mean of additional treatment in fighting eating disorders.The aim of this study is to present the effectiveness of yoga interventions in treatment of eating disorders and importance of screening of yoga communities in terms of higher prevalence of several eating disorder types among those groups. .Within 6 reviewed articles from PubMed database in years 2008-2018, presented research proved the importance of inclusion of yoga interventions in patients with anorexia nervosa, bulimia nervosa, avoidant restrictive food intake disorder, binge eating disorder. Also among yoga communities, higher scores for disorders like orthorexia nervosa, weight control behaviours were found, comparing to non-participants of those practices.Yoga, the ancient practice of finding balance between body, mind and soul, should be furtherly researched and developed in psychiatric practices, due to the effectiveness and promising results proved by presented reviewed studies.